2019
DOI: 10.1111/acel.12965
|View full text |Cite
|
Sign up to set email alerts
|

Molecular footprint of Medawar’s mutation accumulation process in mammalian aging

Abstract: Medawar's mutation accumulation hypothesis explains aging by the declining force of natural selection with age: Slightly deleterious germline mutations expressed in old age can drift to fixation and thereby lead to aging‐related phenotypes. Although widely cited, empirical evidence for this hypothesis has remained limited. Here, we test one of its predictions that genes relatively highly expressed in old adults should be under weaker purifying selection than genes relatively highly expressed in young adults. C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 67 publications
4
16
0
Order By: Relevance
“…This is in contrast to published results for age-biased genes in humans, in which old-biased genes had a significantly higher dN/dS (median: 0.22) than young-biased (median: 0.09, p = 1.4x10 −50 ), as would be expected for a reduction in purifying selection with age (Jia et al, 2018). This was confirmed by a further study on several mammalian tissues, in which an adjusted dN/dS metric correlated more strongly with expression in young compared to old individuals (Turan et al, 2019). To further test the ability of this method to detect a selection shadow in insects, we repeated the analysis for D. melanogaster.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…This is in contrast to published results for age-biased genes in humans, in which old-biased genes had a significantly higher dN/dS (median: 0.22) than young-biased (median: 0.09, p = 1.4x10 −50 ), as would be expected for a reduction in purifying selection with age (Jia et al, 2018). This was confirmed by a further study on several mammalian tissues, in which an adjusted dN/dS metric correlated more strongly with expression in young compared to old individuals (Turan et al, 2019). To further test the ability of this method to detect a selection shadow in insects, we repeated the analysis for D. melanogaster.…”
Section: Resultssupporting
confidence: 58%
“…In the mutation accumulation theory, this 'selection shadow' leads to an accumulation of mutations which have a deleterious effect later in life (Kirkwood and Austad, 2000;Flatt and Partridge, 2018). In support, empirical studies have found that genes with expression biased towards late life are less conserved than those highly expressed at young age across several tissues and mammalian species (Turan et al, 2019;Jia et al, 2018) Building on this, the antagonistic pleiotropy theory describes how genes with beneficial effects early in life can be maintained by selection even if they have pleiotropic negative effects later in life (Williams, 1957). In the disposable soma theory, the pleiotropic effect of more specific genes is described, that cause a trade-off between somatic maintenance and reproduction (Kirkwood, 1977), so that an increased, or early, investment in offspring is expected to come at the price of a shorter lifespan and vice versa (Kirkwood and Austad, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the mutation accumulation theory, this “selection shadow” leads to an accumulation of mutations which have a deleterious effect later in life ( Kirkwood and Austad 2000 ; Flatt and Partridge 2018 ). In support, empirical studies have found that genes with expression biased toward late life are less conserved than those highly expressed at young age across several tissues and mammalian species ( Jia et al 2018 ; Turan et al 2019 ). Building on this, the antagonistic pleiotropy theory describes how genes with beneficial effects early in life can be maintained by selection even if they have pleiotropic negative effects later in life ( Williams 1957 ).…”
Section: Introductionmentioning
confidence: 83%
“…Substituting these results into Eq. (8) shows that p N /p S depends on just three quantities: α m , N e s, and µ N /µ S . The integrals cannot be solved analytically, but the expression for p N /p S can be evaluated numerically.…”
Section: Methodsmentioning
confidence: 96%
“…Jia et al 7 reported that lateexpressed genes in humans have higher rates of nonsynonymous substitution (d N /d S ) and are younger. Turan et al 8 also showed in four additional mammal species that late-expressed genes have higher values of d N /d S . As most nonsynonymous mutations are deleterious while most synonymous mutations evolve neutrally 9 , these results are consistent with Medawar's argument.…”
mentioning
confidence: 91%